Restriction of Private Land Management by the Community from the Perspective of Maslahah Mursalah (Case Study of Runding Village, Panyabungan Barat District, Mandailing Natal Regency) - Rajaindra; Iwan (Warmadewa Press, 2024)
Land is essential for human life, serving as a base for agriculture, housing, and economic activities. In Indonesia, land management and ownership are regulated to benefit both individuals and the community. Conflicts, however, can arise when private land use negatively impacts neighboring areas, as seen in Runding village. Here, a farmer's decision to plant oil palm upstream in Negung village has caused water scarcity for downstream farmers, leading to crop failures. Article 20 of Indonesia's Basic Agrarian Law (UUPA), as explained by Ali Ahmad Chomzah, emphasizes that land ownership rights carry a social function and must not harm others. Land use should adapt to its circumstances and respect community welfare. This aligns with the concept of Maslahah Mursalah in Islamic law, which considers public interest and welfare, derived from the broader goals of Sharia. In Runding village, such restrictions aim to balance individual land use with community welfare, reflecting the principles of public and individual welfare. This research aims to explore the regulatory framework of land ownership rights and how Maslahah Mursalah can guide the management of privately owned land. Using empirical legal research with a case study, statute, and conceptual approach, this study seeks to understand how land management restrictions can ensure both individual rights and societal welfare. The research highlights the potential to balance private land rights with social responsibilities, contributing to sustainable land management practices that align with legal and ethical principles, fostering harmony between landowners and the community.